INVESTIGAÇÃO DO CHLOROVÍRUS ATCV-1 EM AMOSTRAS OROFARÍNGEAS HUMANAS DE UMA POPULAÇÃO NO SUL DO BRASIL Santa Maria, RS 2018 - Oliveira, Élisson Krug (2018)
Introduction: Studies using real-time PCR and next generation sequencing have provided better characterization of the human virome, with identification of unknown viruses, considered the "dark matter" of the microbiome. Viruses with DNA of high molecular weight, which encodes countless proteins including some with biological repercussions, such as some members of viruses of plants of the Phycodnaviridae family, have already been discovered in humans. In this sense, a significant number of viral DNA sequences similar to Acanthocystis turfacea chlorella virus 1 (ATCV-1) were recently identified in samples of human oropharyngeal mucosa in Baltimore (Maryland, USA), with a prevalence of 43.5% in 92 individuals. Its presence was associated with a modest, but measurable, decrease in cognitive functioning, which was tested and reproduced in mice model by more than one group of researchers. Considering the global distribution of the chloroviruses in freshwater and the absence of reproducibility of these findings in individuals from other regions of the world, the aim was to detect ATCV-1 chlorovirus DNA in samples of oropharyngeal mucosa of individuals residents in a city in southern Brazil, as well as to characterize the sociodemographic profile of this population and to verify potential cognitive effects in the presence of the virus. Methods: An observational, cross-sectional and descriptive study was performed at the otorhinolaryngology outpatient clinic of the Casa de Saúde Hospital in the city of Santa Maria (RS, Brazil) from August 2017 to April 2018. A total of 76 volunteers were included, ranging from 18 to 50 years old, residing for at least one year in this city and without acute inflammatory processes in the oropharynx. After sociodemographic identification, clinical otorhinolaryngological evaluation and mini-mental state examination, samples were collected by swabs of the oropharyngeal mucosa for molecular analysis by real-time PCR. The method used was SYBR Green® for the detection of the Z100L gene of the ATCV-1 in the molecular biology laboratory of the Franciscan University. Results: The mini-mental state score correlated with the years of study of the individuals evaluated. . There was no viral detection and, therefore, it was not possible to correlate the ATCV-1 with sociodemographic data or with cognitive alterations. Discussion: The population of study, although geographically distinct, presented sociodemographic variables similar to the population of the only study found in the literature with ATCV-1 in humans. The mini-mental score followed the tendency of the studies to increase with the level of schooling and years of study. Although chloroviruses are distributed worldwide and the prevalence of viral detection in human samples described in a previous study, had been of 43.5%, it is believed that the absence of the virus in natural reservoirs, low viral load in samples or seasonal variations of the chloroviruses may justify the non-detection of ATCV-1 in this population. . Still, there were no signs of contamination of the DNA extraction kit used, which could be a possibility for this viral detection in humans. Conclusion: Thus, ATCV-1 was not observed in Santa Maria population and, for the time being, it can not be considered a potential etiological agent of cognitive alterations in this population, until further studies with this relation may be carried out.